2011
DOI: 10.5005/jp-journals-10021-1023
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Shear Bond Strength of Orthodontic Brackets using Laser Etching and Two Conventional Etching Techniques: An in vitro Study

Abstract: Introduction: The purpose of this study was to evaluate and compare the shear bond strength between the bracket and acid etched enamel, enamel treated with self-etch primer and laser irradiated enamel and to analyze the interface of the enamel bracket bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…This is in agreement with previous studies which used the same radiation power (1.5W) and concluded that adequate etching of orthodontic bonding is achieved when irradiation with a 1.5W laser used. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous studies which used the same radiation power (1.5W) and concluded that adequate etching of orthodontic bonding is achieved when irradiation with a 1.5W laser used. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%